2020
DOI: 10.3389/fneur.2020.553326
|View full text |Cite
|
Sign up to set email alerts
|

The Length of an Infarcted Lesion Along the Perforating Artery Predicts Neurological Deterioration in Single Subcortical Infarction Without Any Relevant Artery Stenosis

Abstract: Objectives: This study aimed to assess image biomarkers of early neurological deterioration in single subcortical infarction (SSI) without any relevant artery stenosis. Methods: Between June 2005 and December 2009, consecutive patients with SSI within 24 h of symptom onset were enrolled. Magnetic resonance angiography of the brain and neck was obtained from all patients to confirm the absence of any stenosis of relevant arteries. We defined early neurological deterioration (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Studies have shown that larger infarct size or lower pons lesions may be associated with a higher probability of progressive motor deficits in patients with basilar artery branch disease (11,28,29). The longitudinal length of the infarcted lesion along the perforating artery was also reported to be associated with END in single subcortical infarction (10). However, there are few studies on the serum markers of END in BAD-stroke patients.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Studies have shown that larger infarct size or lower pons lesions may be associated with a higher probability of progressive motor deficits in patients with basilar artery branch disease (11,28,29). The longitudinal length of the infarcted lesion along the perforating artery was also reported to be associated with END in single subcortical infarction (10). However, there are few studies on the serum markers of END in BAD-stroke patients.…”
Section: Discussionmentioning
confidence: 98%
“…In our study, we observed that approximately 24.1% of the BAD-stroke patients experienced END, which resulted in more severe disability on discharge and higher 3-month MRS scores than the patients without END. Most of the previous studies on predictions of END in patients have focused on imaging features (8)(9)(10)(11)(12)28). Studies have shown that larger infarct size or lower pons lesions may be associated with a higher probability of progressive motor deficits in patients with basilar artery branch disease (11,28,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A binomial logistic regression model was utilized to assess the association between variables and END. The variables imported into the univariate regression analysis were obtained from characteristics with between-group differences in baseline data ( P ≤ 0.1) and the probable risk factors of END that were confirmed in previous studies [age, gender, location in corona radiata, infarction in internal capsule and brainstem [ 4 , 13 , 14 ]; BAD [ 12 ]; visible layers on DWI [ 15 ]; history of diabetes [ 16 ]; blood pressure on admission [ 17 ]; leukocyte count [ 18 ]; glucose [ 19 ]; hypertriglyceridemia [ 20 ]; D-dimer and uric acid [ 21 ]; BUN/CR ratio [ 22 ] and D-dimer [ 23 ]. A multivariate logistic regression model was used to analyze possible independent factors for END and poor function outcome at 3-month after the onset using variables with P ≤ 0.1 in the univariate analysis.…”
Section: Methodsmentioning
confidence: 99%
“…2 B). END was defined as an increase in the NIHSS score ≥ 2 points within the first week after admission [ 13 , 16 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%